2011
DOI: 10.1186/gb-2011-12-2-r17
|View full text |Cite
|
Sign up to set email alerts
|

Stress response regulators identified through genome-wide transcriptome analysis of the (p)ppGpp-dependent response in Rhizobium etli

Abstract: BackgroundThe alarmone (p)ppGpp mediates a global reprogramming of gene expression upon nutrient limitation and other stresses to cope with these unfavorable conditions. Synthesis of (p)ppGpp is, in most bacteria, controlled by RelA/SpoT (Rsh) proteins. The role of (p)ppGpp has been characterized primarily in Escherichia coli and several Gram-positive bacteria. Here, we report the first in-depth analysis of the (p)ppGpp-regulon in an α-proteobacterium using a high-resolution tiling array to better understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
70
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 89 publications
(167 reference statements)
5
70
0
Order By: Relevance
“…Additionally, we and others have recently shown that SR inactivation in P. aeruginosa led to increased oxidant susceptibility (33,57). Conversely, (p)ppGpp accumulation has been associated with oxidative stress tolerance in Streptococcus mutans (58), and transcriptomic studies of (p)ppGpp-regulated genes in Rhizobium etli identified several genes involved in oxidative stress resistance (59).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we and others have recently shown that SR inactivation in P. aeruginosa led to increased oxidant susceptibility (33,57). Conversely, (p)ppGpp accumulation has been associated with oxidative stress tolerance in Streptococcus mutans (58), and transcriptomic studies of (p)ppGpp-regulated genes in Rhizobium etli identified several genes involved in oxidative stress resistance (59).…”
Section: Discussionmentioning
confidence: 99%
“…One important gene that showed increased expression after long-term starvation was the gene encoding a homologue of the (p)ppGpp synthase gene. (p)ppGpp is known as a master regulator of gene expression during stress conditions (Atkinson et al, 2011) and is required for regulation of gene expression during starvation or the non-growing state of cells in a number of bacteria including E. coli and Rhizobium etli (Traxler et al, 2008;Vercruysse et al, 2011). Starved cells of LH128 also expressed genes that encode RNases, such as RNaseE, which degrade rRNA during starvation stress.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, accumulation of ppGpp activates LEE gene expression and increases bacterial adherence (32). In plant-associated pseudomonads and rhizobia, ppGpp affects epiphytic fitness, biocontrol activity, biofilm formation, and hydrogen peroxide and antibiotic tolerance, as well as nodulation (33)(34)(35)(36). In plant-pathogenic bacteria, ppGpp is required for cell wall-degrading enzyme production, quorum sensing signal degradation, and Ti plasmid transfer (37)(38)(39).…”
mentioning
confidence: 99%